Analysis of Phenotypic Characteristics and Sucrose Metabolism in the Roots of Raphanus sativus L. - Kang, Ji-Nam; Kim, Jung Sun; Lee, Si Myung; Won, So Youn; Seo, Mi-Suk; Kwon, Soo-Jin (Frontiers in Plant Science, 2021)
The taproot of radish (Raphanus sativus L.) is an important sink organ; it is morphologically diverse and contains large amounts of secondary metabolites. Sucrose metabolism is believed to be important in the development of sink organs. We measured the amounts of glucose, fructose, and sucrose in the roots of sixty three radish accessions and analyzed the association between the sugar content and the root phenotype. Fructose content correlated with the root color and length characteristics, glucose was the most abundant sugar in the roots, and the sucrose content was very low, compared to that of the hexoses in most of the accessions. Expression analysis of the genes involved in sucrose metabolism, transportation, starch synthesis, and cell wall synthesis was performed through RNA sequencing. The genes encoding sucrose synthases (SUSY) and the enzymes involved in the synthesis of cellulose were highly expressed, indicating that SUSY is involved in cell wall synthesis in radish roots. The positive correlation (R score) between the sucrose content and the expression of cell wall invertase and sugar transporter proteins suggest that hexose accumulation could occur through the apoplastic pathway in radish roots. A positive R score was also obtained when comparing the expression of genes encoding SUSY and fructokinase (FK), suggesting that the fructose produced by SUSY is mostly phosphorylated by FK. In addition, we concluded that sucrose was the most metabolized sugar in radish roots.